PERENCANAAN LANSKAP SUNGAI SAMBAS KECIL BERBASIS NILAI MANFAAT DI KOTA SAMBAS, KALIMANTAN BARAT - Nuraini, .; Makalew, Afra DN; Nurisjah, Siti (http://arl-faperta.ipb.ac.id/, 2016)
Sambas Kecil River area in Sambas City is a center of city growth, business, fishery, agriculture, and circulation of the society. The High intensity of utilization and the rapid development in the city, created degradation of the quality of the river and decreased the urban view, human health, transportation, social culture, economic, and recreation activity.This study aims to characterize the utilization and landscape plan based on benefit value for sustainability of Sambas River areas. The method that used was descriptive both qualitative and quantitative. Planning was used process and stages by Gold (1980). The result of analysis showed that the Sambas Kecil River area divided by three ecological sensitivities i.e. low (12.6 km), moderate (17.8 km), and high (12.6 km). The high sensitivity dominated by forest, the moderate dominated by agriculture and settlement, and the low dominated by settlement. Variety of activities are divided into three aspects i.e. social aspect, cultural aspect, and economic aspect. This planning based on benefit value of ecological and sustainability for Sambas Kecil River area and able to restore and maintain the natural character of the river. The result of integration of the river character and utilization created three plan models i.e. natural, semi-natural, and built areas of the development river landscape plan. This plan is expected to restore the value of the benefits of the river through the area management by local communities so they can feel directly the benefits from the existence of the river, and they will able to preserve the river sustainably.